2014
DOI: 10.1111/flan.12113
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Modality Input in Repeated Reading for Foreign Language Learners With Different Learning Styles

Abstract: Research into dual‐modality theory has long rested on the assumption that presenting input in two modalities leads to better learning outcomes. However, this may not always hold true. This study explored the possible advantages of using dual modality in repeated reading—a pedagogy often used to enhance reading development—for two literacy purposes, second language (L2) reading comprehension and vocabulary development. Furthermore, the study probed whether the efficacy of repeated reading implemented using both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…The results of this study showed that the module was effective in achieving its goals. The results support those from the study done by Liu and Todd [24] that the repeated reading practice should be best implemented visà-vis the purposes of L2 reading and vocabulary learning. Pillinger and Wood [25] and Mason [26] revealed repeated reading will increase the improvements of the kindergarten children in writing vocabulary and word reading scores.…”
Section: Discussion and Interpretationsupporting
confidence: 87%
“…The results of this study showed that the module was effective in achieving its goals. The results support those from the study done by Liu and Todd [24] that the repeated reading practice should be best implemented visà-vis the purposes of L2 reading and vocabulary learning. Pillinger and Wood [25] and Mason [26] revealed repeated reading will increase the improvements of the kindergarten children in writing vocabulary and word reading scores.…”
Section: Discussion and Interpretationsupporting
confidence: 87%
“…results of L1 studies by Kosciolek & Ysseldyke, 2000;McKevitt & Elliott, 2003;Meloy, Deville, & Frisbie, 2002). The reason for these findings might be that our participants, regardless of their official dyslexia status, might have been already at the stage of reading development where in the case of relatively easy texts they did not need to rely on the additional support of the read-aloud relating to the phonological information of word forms, sentence stress and intonation (Liu & Todd, 2014). Another possible explanation might be that because the texts were short and comprehension questions asked about factual information, the benefits of the joint visual and auditory information (Moreno & Mayer, 2002;Paivio, 1991) could not be detected.…”
Section: Discussionmentioning
confidence: 80%
“…In the framework of a repeated reading programme, Liu and Todd (2014) examined the effectiveness of different types of dual-modal (visual and oral) and single-modal input on text comprehension and vocabulary learning. In the dual-modal input conditions learners of Japanese as a foreign language listened to a text being read out to them and either (1) shadowed the teacher by saying out loud what they heard, (2) imitated the teacher after a time lapse, or (3) read along with the teacher vocalizing the text in their minds.…”
Section: Test Fairness and Accommodations For Dyslexic Test-takersmentioning
confidence: 99%
“…According to Peacock (2001), despite a wealth of theoretical arguments in favor of matching learning style with instruction, no empirical evidence can be found to support the issue in L2 acquisition research. However, as noted by Liu and Todd (2014), the contradictory results of previous studies regarding the benefits of instruction which is catered to learners’ style preferences do not mean that style-based instruction is ineffective and instead it indicates a need for further studies to shed further light on this issue.…”
Section: Introductionmentioning
confidence: 98%